Tolstoy and spirituality - Cicovacki, Predrag; Grek, Heidi Nada (Academic Studies Press, 2018)
This interdisciplinary collection of essays examines Leo Tolstoy's unorthodox and provocative approach to spirituality, as presented in his numerous literary and his philosophico-religious works. The collection includes twelve contributions written for this volume. Its contributors are writers, philosophers, literary critics, and experts in Russian literature. Six of the essays examine Tolstoy's literary works while the other six scrutinize more closely his philosophical views. The two central foci of examination are The Kreutzer Sonata and The Kingdom of God is within You.